Discussion with Sinodo Dili: The Social Role of the Church in Timor Leste - Posma Sariguna Johnson Kennedy (Journal of Sustainable Community Development (JSCD), 2022)
The implementation of this community service aims to deepen issues regarding the role of the Church in Timor Leste in dealing with social problems in serving and protecting its people through discussions with Sinodo in Dili, Timor Leste. This topic needs to be explored because Timor Leste is a neighboring country of Indonesia. It is directly adjacent to the Province of Nusa Tenggara Timur, so it is necessary to know its character and socio-culture so that friendship between countries can be carried out properly, especially in managing state borders that prioritize welfare. The Church in Timor Leste should have a balanced appearance, that is, in worship/sacrament appearances and social appearances. Good cooperation is needed between the hierarchy (church leaders) and the laity (the people) to mobilize the Church's role in overcoming social conditions or situations among the people or society. The role of the Church has been relentless, starting from the Timor-Portugal period and through the Timor-Indonesian period to the present-day Independent Timor.